2013
DOI: 10.4097/kjae.2013.64.2.133
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind study to evaluate the efficacy of ramosetron and palonosetron for prevention of postoperative nausea and vomiting after gynecological laparoscopic surgery

Abstract: BackgroundPostoperative nausea and vomiting (PONV) is a common complication after anesthesia and surgery; 5-hydroxytryptamine type 3 (5-HT3) receptor antagonists have been considered as a first-line therapy. Ramosetron and palonosetron are more recently developed drugs and have greater receptor affinity and a longer elimination half-life compared with older 5-HT3 receptor antagonists. The purpose of this study was to determine which drug is more effective for preventing PONV between ramosetron and palonosetron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…Our results were similar to Park SK, who found that the incidence of PONV between the Ramosetron group and the Palonosetron group did not demonstrate a difference during the 0-48 hour time period. [27] Our study results were comparable to Fuji Y et al, who found no difference between Granisetron and Ramosetron for prevention of PONV for a period of 0-24 hours after anaesthesia. [28] There was statistically significant difference regarding complete response during 4-24 hours postoperatively between Palonosetron and Granisetron.…”
Section: Discussionsupporting
confidence: 88%
“…Our results were similar to Park SK, who found that the incidence of PONV between the Ramosetron group and the Palonosetron group did not demonstrate a difference during the 0-48 hour time period. [27] Our study results were comparable to Fuji Y et al, who found no difference between Granisetron and Ramosetron for prevention of PONV for a period of 0-24 hours after anaesthesia. [28] There was statistically significant difference regarding complete response during 4-24 hours postoperatively between Palonosetron and Granisetron.…”
Section: Discussionsupporting
confidence: 88%
“…The 5-HT 3 antagonists (palonosetron and ramosetron) were administrated during the early phase of the operation in four studies [14–16,19] and at the end of the surgery in four [17,18,20,21]. …”
Section: Resultsmentioning
confidence: 99%
“…Five studies [14,15,17,19,20] assessed the effectiveness of palonosetron and of ramosetron on early and four studies assessed the effectiveness of each drug on late PONV [15,17,19,20] and seven studies on overall PONV [14,15,1721]. The combined results could not reveal the differences between the effectiveness of palonosetron and that of ramosetron on early PONV (RR 1.07; 95% CI, 0.60 to 1.92; P chi 2 = 0.03; I 2 = 63%; NNT 25.8; 95% CI, NNTH 8.7 to ∞ to NNTB 26.3), late PONV (RR 0.92; 95% CI 0.72 to 1.19; P chi 2 = 0.14; I 2 = 44.4%; NNTB 74.1; 95% CI, NNTH 14.4 to ∞ to NNTB 10.4) or overall PONV (RR 1.23; 95% CI 0.82 to 1.85; P chi 2 = 0.034; I 2 = 56.1%; NNTB 14.4; 95% CI, NNTH 7.2 to ∞ to NNTB 1957.8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were shown by Park et al that is level of satisfaction was higher in ramosetron group as compared to Palonosetron, though it was not statistically significant (p>0.05). 20 Another study revealed no significant difference between level of satisfaction in between two groups (p>0.05). 21 In present study, we could not make out gender differences as far as response of the drugs are concerned.…”
Section: Discussionmentioning
confidence: 90%